c - Hallesby, Ole; Cho Kye-gwang omgim (Seoul : Kyujang, 2010)
"My desire and my prayer have been this: to preach the gospel of prayer, without shutting down the laws of prayer." Ole Hallesby Since the book came out for the first time in 1927, it has inspired tens of thousands of people for prayer and prayer service. With its simple and direct style, its warm and intrusive voice and its honest and soul-orientated approach, Ole Hallesby has given us a classic in prayer literature, which continues to reach new generations with their radical message of power in the folded hands. Ole Hallesby was one of the most central leaders in Norwegian layman movement through the first you of the 20th century. He was a professor of systematic theology at the Parish Faculty, teaches at Bible School in Staffeldtsgate and took a number of initiatives to establish Christian activities.
Translated from the Norwegian -- Prayer by Ole Hallesby
Keywords: Prayer -- Religious aspects -- Christianity